The Berkeley Manuscript: a New Critical Text and Translation - Ellsworth, Oliver B. (Lincoln and London University of Nebraska Press, 1984)
The treatises collected here in this work consider topics as fundamental and diverse as counterpoint, notation, tuning, chant, and speculative matters, for example, the history of the development of the scale. Extensive notes, a critical introduction, and indexes rerum et verborum augment this volume.
Keywords: Music history; Tuning